Determinants of Outmigration: A Micro-econometric Analysis - Acharya, Sabitri Devi (Economic Journal of Development Issues, 2020)
Remittances, what foreign workers send back to their home countries, have grown not only in size but in importance for many developing countries. Remittances are integral to migration because one of the basic motives for migrating is to remit a portion of earnings to the communities of origin or households. Remittances, as part of the migration process, can be viewed as a family income maximisation strategy. The general objective of this study is to examine the determinants of outmigration at household level. The study adopts the micro- econometrics research design by utilizing cross-sectional household survey data. Two types of factors: pull and push factors drive outmigration. The findings indicate that education, ecological belt, consumption quintile, access to government facilities and the ratio of food expenditure to total expenditures are determinants of outmigration.